2014
DOI: 10.4238/2014.november.27.7
|View full text |Cite
|
Sign up to set email alerts
|

Selection of optimized candidate reference genes for qRT-PCR normalization in rice (Oryza sativa L.) during Magnaporthe oryzae infection and drought

Abstract: ABSTRACT. Drought and rice blast disease caused by Magnaporthe oryzae are two of the most serious threats to global rice production. To explore the mechanisms underlying gene expression induced in rice by stresses, studies involving transcriptome analyses have been conducted over the past few years. Thus, it is crucial to have a reliable set of reference genes to normalize the expression levels of rice genes affected by different stresses. To identify potential reference genes for studies of the differential e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 35 publications
3
24
0
Order By: Relevance
“…Based on the results presented here, of the nine candidate genes, 18S, CYCOL, and GAPDH performed poorly. These results agree with those found in other studies (Bevitori et al, 2014). In contrast, TIP, EF, Clathrin and BHLH were good candidates for normalization in Lilium x formolongi across all samples.…”
Section: Discussionsupporting
confidence: 81%
“…Based on the results presented here, of the nine candidate genes, 18S, CYCOL, and GAPDH performed poorly. These results agree with those found in other studies (Bevitori et al, 2014). In contrast, TIP, EF, Clathrin and BHLH were good candidates for normalization in Lilium x formolongi across all samples.…”
Section: Discussionsupporting
confidence: 81%
“…species, such as rice [14], rubber tree [15], sunflower [16], black locust [17], grapevine [18], and annual ryegrass [19]. species, such as rice [14], rubber tree [15], sunflower [16], black locust [17], grapevine [18], and annual ryegrass [19].…”
mentioning
confidence: 99%
“…The RT-qPCR approach provides greatly enhanced levels of sensitivity and accuracy for gene expression analysis compared to the more conventional methods, semi-quantitative RT-PCR and northern blot hybridisation [7]. The RT-qPCR approach is reliant upon the exponential incorporation of fluorescent dyes into amplified products [8], and has become the method of choice to validate RNA sequencing (RNA-Seq) data, or to quantify the abundance of a select group of target genes stemming from a large population of expressed transcripts [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…Further, due to their assigned function, the expression of a housekeeper gene is assumed constant irrespective of the organ or tissue type under analysis, or the developmental stage or physiological condition(s) of the assessed species [13, 14]. Several housekeeper genes have been widely used in Arabidopsis thaliana ( CYCLOPHILIN ( CYC ), ACTIN2 ( ACT2 ) and ELONGATION FACTOR 1 α ( EF1 α; [15, 16])), rice ( ACTIN1 ( ACT1 ) and UBIQUITIN5 ( UBI5 ; [7, 11])), and sorghum ( SERINE / THERONINE - PROTEIN PHOSPHATASE 2A ( PP2A ) and EUKARYOTIC INITIATION FACTOR 4α ( EIF4α ; [14])). However, a growing body of research has shown that housekeeper genes cannot be utilised universally across different plant species, experimental conditions, or even across different developmental stages within a single species [9, 11, 14].…”
Section: Introductionmentioning
confidence: 99%